Nurse educator education in six European countries: a descriptive study / Ausbildung von Pflegepädagog/-innen in sechs europäischen Ländern – eine deskriptive Studie - Campos Silva Simone; Salminen Leena; Elonen Imane; Linares Pilar Fuster; Cassar Maria; Haycock-Stuart Elaine; Saaranen Terhi; Zrubcová Dana; Ewers Michael (Poland, 2022)
Within Europe, education and licensing requirements for selected health professions have been harmonised in order to enable the free movement within a unified labour market. The regulations of these professions include requirements for the necessary level and content of education in each profession that help to meet the needs of the various healthcare systems and to ensure a minimum level of competence of health professionals throughout Europe (Directive 2013/55/EU, 2013, Art. 31). It is remarkable, however, that nurse educators are not considered in this goal of regulating and standardising the healthcare professions. In its Global Strategic Directions for Nursing and Midwifery, the World Health Organisation (WHO) identifies nurse education as highly important when it comes to meeting the global need for skilled nurses (WHO, 2021). Nurse educators who are educated with a high standard are an absolute necessity for meeting this need. At the same time, the WHO draws attention to a widely documented shortage of qualified nurse educators both in institutional educational settings and in nursing practice (WHO, 2021)—a paradox that urgently requires greater attention both politically and in research.
A three-year development project funded by the European Union (EU) via ERASMUS+ addresses this paradox by examining the current practice of nurse educator education. Entitled A New Agenda for Nurse Educator Education Within Europe (webpage: https://new-nurse-educator.utu.fi), the project involves seven universities in the six European countries of Finland (FI), Germany (DE), Malta (MT), Slovakia (SK), Spain (ES), and the United Kingdom (UK). The main objectives are to narrow knowledge gaps in nurse educator educational preparation; to explore competencies and continuous education needs; to discuss strategies for the potential harmonisation of nurse educator education in these countries; and to develop, implement, and evaluate a joint study programme for future nurse educators in Europe.